Keabsahan Hak Tanggungan Elektronik Yang Terbit Tanpa Adanya Pemeriksaan Oleh Pejabat Yang Berwenang - Swandewi, I Gusti Ayu Hary; Purwanto, I Wayan Novy (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
This study aims to determine the validity of electronic-based mortgages that are issued, without any prior inspection. This article used a normative legal research methodology focusing on positive law. The findings of this study lead to the provisions of the National Land Law that the only guarantee for land in Indonesia is mortgage rights. 'Property rights, Business Use Rights, Building Use Rights, and use rights over state land' are among the land rights that can be encumbered with mortgage rights. These rights must be registered according to their terms and can be transferred according to their nature because the Head of the Office at the Land Office, or an officer that has been given the authority is administratively responsible for e-Mortgage and its services that are issued without inspection. With the inclusion of the digital signature, the signature has the same legal force and consequences as the signature of an authorized official which is done manually. The validity of the e-Mortgage issued without any inspection by the competent authority is the same as the e-Mortgage issued after the examination.